R-t-b based permanent magnet

JP2024092719A5Pending Publication Date: 2025-11-06TDK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022208847
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-12-26
Publication Date
2025-11-06

AI Technical Summary

Technical Problem

Existing R-T-B permanent magnets face challenges in achieving a well-balanced improvement in residual magnetic flux density (Br) and coercive force (HcJ) at room temperature, with a high squareness ratio (Hk/HcJ) being difficult to attain.

Method used

The R-T-B permanent magnet composition is optimized with specific ranges for rare earth elements (TRE), transition metals, boron, and additional elements like Al, Cu, Ga, and Zr, along with controlled manufacturing processes to ensure balanced magnetic properties.

Benefits of technology

The solution results in an R-T-B permanent magnet with improved Br and HcJ at room temperature, along with a high Hk/HcJ ratio, enhancing its magnetic performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide an R-T-B based permanent magnet which is improved in Br at a room temperature and HcJ at a room temperature and which is also high in Hk / HcJ.SOLUTION: There is provided an R-T-B based permanent magnet containing a rare earth element, a transition metal element, boron and M. The R-T-B based permanent magnet contains at least Nd and Pr as the rare earth element. M is one or more elements selected from among Al, Cu, Ga, and Zr. When TRE represents a content of the rare earth element, and Pr / TRE represents a value obtained by dividing a content of Pr by TRE, TRE is 29.00 mass% or more and 31.00 mass% or less, a content of a heavy rare earth element is 0 mass% or more and 0.20 mass% or less, Pr / TRE is 0.30 or more and 0.50 or less, a content of boron is 0.90 mass% or more and 1.00 mass% or less, a content of carbon is 0 mass% or more and 0.10 mass% or less, a content of oxygen is 0 mass% or more and 0.15 mass% or less, a content of nitrogen is 0 mass% or more and 0.15 mass% or less, and a content of M is 0.30 mass% or more and 1.50 mass% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an RTB-based permanent magnet. [Background technology]

[0002] Patent Document 1 describes an invention relating to a manufacturing method for an RTB based sintered magnet, in particular a method of diffusing a heavy rare earth element RH into an RTB based sintered magnet material.

[0003] Patent Document 2 describes an invention related to rare earth magnets. In particular, the two-particle grain boundary phase has a magnetic property different from that of the ferromagnetic material, for example, R6T 13 A rare earth magnet consisting of M phases is described.

[0004] Patent Document 3 describes an invention related to a manufacturing method for anisotropic rare earth magnets. In particular, it describes a manufacturing method in which a quenched ribbon with an amorphous structure is sintered, and then heated during hot working to crystallize and anisotropize the magnet.

[0005] Patent Document 4 describes an invention related to a method for producing an RTB sintered magnet. In particular, the method describes a magnet production method characterized by making the Pr content 75 mass% or more of the total R, and lengthening the sintering time according to the ratio of Pr to R. Magnets obtained by this production method have high Br at low temperatures and high Hk / HcJ at room temperature. The low temperature in Patent Document 4 is -180°C±20°C. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 121790 [Patent Document 2] JP 2014-209546 A [Patent Document 3] JP 2012-23190 A [Patent Document 4] Patent Publication No. 2021-155782 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of an exemplary embodiment of the present invention is to provide an RTB permanent magnet that exhibits a well-balanced improvement in remanence (Br) at room temperature and coercivity (HcJ) at room temperature, as well as a high squareness ratio (Hk / HcJ).

[0008] Unless otherwise specified, the magnetic properties below refer to magnetic properties at room temperature (23.0°C ± 1.0°C). [Means for solving the problem]

[0009] The RTB permanent magnet of the exemplary embodiment of the present invention is an RTB permanent magnet including a rare earth element, a transition metal element, boron, and M, The rare earth elements include at least Nd and Pr, The transition metal element contains at least Fe, or Fe and Co, M is one or more selected from Al, Cu, Ga, and Zr; The content of the rare earth element on a mass basis is defined as TRE, and the content of Pr on a mass basis divided by TRE is defined as Pr / TRE. TRE is 29.00 mass% or more and 31.00 mass% or less, The content of heavy rare earth elements is 0% by mass or more and 0.20% by mass or less, Pr / TRE is 0.30 or more and 0.50 or less, The boron content is 0.90% by mass or more and 1.00% by mass or less, The carbon content is 0% by mass or more and 0.10% by mass or less, The oxygen content is 0% by mass or more and 0.15% by mass or less, The nitrogen content is 0% by mass or more and 0.15% by mass or less, The content of M is 0.30 mass % or more and 1.50 mass % or less.

[0010] The Pr / C value obtained by dividing the Pr content by the carbon content by mass may be 100 or more.

[0011] The Cu content may be 0 mass % or more and 0.20 mass % or less.

[0012] The total content of boron and carbon may be 0.93 mass % or more and 1.07 mass % or less.

[0013] The content of M may be 0.50% by mass or more and 1.00% by mass or less. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Hereinafter, an embodiment of the present invention will be described.

[0015] In the RTB permanent magnet, R represents a rare earth element, T represents a transition metal element, and B represents boron. The rare earth element represents scandium (Sc), yttrium (Y), and lanthanoid. T may represent an iron group element. That is, T may represent one or more elements selected from iron (Fe), cobalt (Co), and nickel (Ni). The RTB permanent magnet is R2T 14 Contains main phase grains with B-type crystal structure. R2T 14 A part of the boron contained in the B-type crystal structure may be replaced by carbon. 14 In the case of "B-type crystal structure," the transition metal element T does not include the rare earth element R.

[0016] The RTB permanent magnet according to this embodiment contains at least a rare earth element, a transition metal element, boron, and M. The RTB permanent magnet according to this embodiment contains at least neodymium (Nd) and praseodymium (Pr) as rare earth elements. The RTB permanent magnet according to this embodiment contains at least Fe, or Fe and Co, as transition metal elements. M is one or more selected from aluminum (Al), copper (Cu), gallium (Ga), and zirconium (Zr).

[0017] The content of each component contained in the RTB permanent magnet is described below, but unless otherwise specified, the content is when the RTB permanent magnet is 100 mass%. Taking the RTB permanent magnet as 100 mass% means that the total content of all elements is 100 mass%.

[0018] The content of rare earth elements in the RTB permanent magnet on a mass basis is defined as TRE, and the TRE is 29.00 mass% or more and 31.00 mass% or less. It may be 30.00 mass% or less and 31.00 mass% or less. If the TRE is too small, the HcJ decreases. If the TRE is too large, the Br decreases.

[0019] Among the rare earth elements, gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu) are classified as heavy rare earth elements (RH), and the other rare earth elements are classified as light rare earth elements (RL).

[0020] There are no particular limitations on the type of RL contained in the RTB permanent magnet, other than that at least Nd and Pr are contained. There are no particular limitations on the total content of Nd and Pr. For example, it may be 29.00 mass% or more and 31.00 mass% or less. Other RL may be contained within a range that does not significantly impair the magnetic properties of the RTB permanent magnet. Specifically, the total content of RL other than Nd and Pr may be 0 mass% or more and 0.20 mass% or less.

[0021] The total content of RH in the RTB permanent magnet is 0% by mass or more and 0.20% by mass or less. In other words, the RTB permanent magnet does not need to contain RH. There are no particular limitations on the type of RH contained in the RTB permanent magnet. For example, it may be one or more types selected from Gd, Tb, Dy, and Ho, or one or more types selected from Tb, Dy, and Ho. If the content of RH is too high, Br decreases.

[0022] The Pr / TRE value obtained by dividing the Pr content by TRE on a mass basis is Pr / TRE, and the Pr / TRE in the RTB permanent magnet is 0.30 or more and 0.50 or less. In other words, the proportion of Pr in the rare earth elements contained in the RTB permanent magnet is 30% or more and 50% or less on a mass basis. Pr / TRE may be 0.40 or more and 0.50 or less. If Pr / TRE is too small, HcJ decreases. If Pr / TRE is too large, Hk / HcJ is likely to decrease.

[0023] RTB permanent magnets contain at least Fe, or Fe and Co. There are no particular limitations on the Co content in RTB magnets. For example, it may be 0% by mass or more and 2.00% by mass or less, or 1.10% by mass or more and 1.50% by mass or less. If the Co content is more than 2.00% by mass, the raw material cost is likely to increase. In particular, from the viewpoint of reducing costs while maintaining high properties, the Co content may be 0% by mass or more and 0.50% by mass or less.

[0024] The boron content in the RTB permanent magnet (hereinafter, boron may be simply referred to as B) is 0.90% by mass or more and 1.00% by mass or less. It may be 0.90% by mass or more and 0.95% by mass or less. If the B content is too low, Hk / HcJ is likely to decrease. If the B content is too high, HcJ is likely to decrease.

[0025] The carbon content in the RTB permanent magnet (hereinafter, carbon may be simply referred to as C) is from 0% by mass to 0.10% by mass. In other words, the RTB permanent magnet does not have to contain C. The C content may be from 0.02% by mass to 0.09% by mass. When an RTB permanent magnet with a C content of less than 0.02% by mass is produced, the efficiency of fine pulverization decreases. If the C content is too high, the HcJ decreases.

[0026] The total content of B and C in the RTB permanent magnet (hereinafter sometimes simply referred to as B+C) may be 0.93% by mass or more and 1.07% by mass or less, or 0.93% by mass or more and 1.02% by mass or less. By keeping B+C within the above range, Br and HcJ tend to be further improved.

[0027] The Pr / C value obtained by dividing the Pr content by the C content by mass may be 100 or more, or 150 or more. There is no particular upper limit to Pr / C. For example, Pr / C may be 600 or less, or 400 or less. A Pr / C of 100 or more makes it easier to further improve HcJ.

[0028] The oxygen content in the RTB permanent magnet (hereinafter, oxygen may be simply referred to as O) is from 0 mass% to 0.15 mass%. In other words, the RTB permanent magnet does not have to contain O. The O content may be from 0.04 mass% to 0.15 mass%, or from 0.04 mass% to 0.10 mass%. Manufacturing an RTB permanent magnet with an O content of less than 0.04 mass% increases manufacturing costs. If the O content is too high, HcJ decreases.

[0029] The nitrogen content in the RTB permanent magnet (hereinafter, nitrogen may be simply referred to as N) is from 0 mass% to 0.15 mass%. In other words, the RTB permanent magnet does not have to contain N. The N content may be from 0.03 mass% to 0.10 mass%, or from 0.05 mass% to 0.07 mass%. Manufacturing an RTB permanent magnet with an N content of less than 0.03 mass% increases manufacturing costs. If the N content is too high, HcJ decreases.

[0030] The M content in the RTB permanent magnet, i.e., the total content of Al, Cu, Ga and Zr, is 0.30% by mass or more and 1.50% by mass or less. It may be 0.50% by mass or more and 1.00% by mass or less, or may be 0.65% by mass or more and 1.00% by mass or less. If the M content is too low, HcJ decreases.

[0031] The Cu content in the RTB permanent magnet may be 0% by mass or more and 0.40% by mass or less, 0% by mass or more and 0.20% by mass or less, 0.05% by mass or more and 0.20% by mass or less, or 0.05% by mass or more and 0.19% by mass or less. A Cu content of 0.20% or less by mass makes it easier to improve HcJ, and a Cu content of 0.19% or less by mass makes it easier to further improve HcJ.

[0032] The Al content in the RTB permanent magnet may be 0.02% by mass or more and 0.35% by mass or less, or may be 0.05% by mass or more and 0.20% by mass or less.

[0033] The Zr content in the RTB permanent magnet may be from 0 mass % to 0.35 mass %, from 0.15 mass % to 0.35 mass %, or from 0.20 mass % to 0.35 mass %.

[0034] The Ga content may be from 0% by mass to 0.50% by mass, from 0.20% by mass to 0.40% by mass, or from 0.25% by mass to 0.40% by mass.

[0035] There is no particular limit to the Fe content in the RTB permanent magnet. The Fe content in the RTB permanent magnet may be substantially the remainder of the RTB permanent magnet. Specifically, the content of elements other than rare earth elements, Fe, Co, B, C, O, N, and M (e.g., Nb, Si, Mg, Mn, Zn, etc.) may each be 0% by mass or more and 0.05% by mass or less.

[0036] The content of elements other than rare earth elements, Fe, Co, B, C, O, N and M in the RTB permanent magnet (for example, Nb, Si, Mg, Mn, Zn, etc.) may be 0% by mass or more and 0.01% by mass or less.

[0037] The total content of elements other than rare earth elements, Fe, Co, B, C, O, N and M in the RTB permanent magnet may be 0% or more and 0.50% or less by mass.

[0038] Elements in the RTB permanent magnet other than the rare earth elements, Fe, Co, B and M (e.g., C, O, N, Nb, Si, Mg, Mn, Zn, etc.) may be intentionally added during the production of the RTB permanent magnet described below, or may be contained as impurities derived from the raw materials of the RTB permanent magnet.

[0039] When the RTB permanent magnet has the above composition, the Br at room temperature and the HcJ at room temperature are improved in a well-balanced manner, and an RTB permanent magnet with a high Hk / HcJ can be obtained.

[0040] In general, the smaller the Pr / TRE in an RTB permanent magnet, the better the temperature characteristics of the RTB permanent magnet, and the smaller the decrease in coercivity when the temperature rises. Also, when a didymium alloy consisting essentially of only Nd and Pr and having a Pr / TRE of about 0.20 to 0.25 is used as the raw material for the light rare earth elements, the raw material cost in manufacturing the RTB permanent magnet tends to be the lowest. Whether the Pr / TRE in the RTB permanent magnet is larger or smaller than the Pr / TRE in the didymium alloy, the raw material cost tends to increase.

[0041] The inventors have discovered that by setting Pr / TRE in an RTB permanent magnet to be between 0.30 and 0.50, and keeping the contents of other elements within specified ranges, it is possible to obtain an RTB permanent magnet that achieves a balanced improvement in the residual magnetic flux density (Br) at room temperature and the coercive force (HcJ) at room temperature, and also has a high squareness ratio (Hk / HcJ).

[0042] <Method for manufacturing R-T-B system permanent magnet> Hereinafter, an example of a method for manufacturing an R-T-B system permanent magnet according to this embodiment will be described. The method for manufacturing an R-T-B system permanent magnet (R-T-B system sintered magnet) according to this embodiment has the following steps. Note that each of the steps (g) to (i) shown below may be omitted.

[0043] (a) Alloy preparation step of preparing a raw material alloy (b) Crushing step of crushing the raw material alloy (c) Molding step of molding the obtained alloy powder (d) Sintering step of sintering the molded body to obtain an R-T-B system permanent magnet (e) Aging treatment step of aging the R-T-B system permanent magnet (f) Cooling step of cooling the R-T-B system permanent magnet (g) Processing step of processing the R-T-B system permanent magnet (h) Grain boundary diffusion step of diffusing a heavy rare earth element into the grain boundary of the R-T-B system permanent magnet (i) Surface treatment step of performing surface treatment on the R-T-B system permanent magnet

[0044] [Alloy preparation step] First, a raw material alloy is prepared (alloy preparation step). Hereinafter, the strip casting method will be described as an example of the alloy preparation method, but the alloy preparation method is not limited to the strip casting method.

[0045] First, raw material metals corresponding to the composition of the raw material alloy are prepared, and the raw material metals prepared in an inert gas atmosphere such as vacuum or Ar gas are melted. Then, the melted raw material metals are poured onto a metal rotating roll, rapidly cooled, and then crushed to produce a flaky raw material alloy. Note that in this embodiment, the single alloy method will be described, but the two alloy method in which two alloys, a first alloy and a second alloy, are mixed to produce a raw material alloy may also be used.

[0046] There is no particular limit to the type of raw material metal. For example, rare earth metals, alloys such as rare earth alloys such as pure iron and pure cobalt, and / or compounds such as ferroboron can be used. There is no particular limit to the casting method for casting the raw material metal. For example, ingot casting, strip casting, book molding, centrifugal casting, etc. can be used. If the obtained raw material alloy has solidification segregation, it may be subjected to homogenization treatment (solution treatment) as necessary.

[0047] [Crushing process] After the raw alloy is prepared, the raw alloy is pulverized (pulverization step). The pulverization step may be performed in two stages, a coarse pulverization step in which the alloy is pulverized to a particle size of several hundred μm to several mm, and a fine pulverization step in which the alloy is pulverized to a particle size of several μm, or may be performed in a single stage, the fine pulverization step alone.

[0048] (Coarse grinding process) The raw alloy is coarsely pulverized until the particle size is about several hundred μm to several mm (coarse pulverization step). This produces a coarsely pulverized powder of the raw alloy. The coarse pulverization may be performed, for example, by hydrogen absorption pulverization. In general, when hydrogen is absorbed into the raw alloy, each phase constituting the raw alloy may expand. The hydrogen absorption pulverization can be performed by causing self-disintegrating pulverization due to the difference in the volume expansion rate between different phases when hydrogen is absorbed into the raw alloy.

[0049] The coarsely pulverized powder obtained by hydrogen absorption pulverization may be dehydrogenated. There is no particular limitation on the method of dehydrogenation. For example, the coarsely pulverized powder may be heated to release hydrogen. There is no particular limitation on the heating conditions when the coarsely pulverized powder is heated to release hydrogen. For example, the powder is heated at 300 to 650°C in an argon flow or in a vacuum.

[0050] The method of coarse pulverization is not limited to the above hydrogen absorption pulverization. For example, coarse pulverization may be performed using a coarse pulverizer such as a stamp mill, a jaw crusher, or a Braun mill in an inert gas atmosphere. When performing coarse pulverization using these methods, dehydrogenation is not required.

[0051] In order to obtain an RTB permanent magnet with high magnetic properties, it is preferable that the atmosphere in each step from the coarse crushing step to the sintering step described below be an atmosphere with a low oxygen concentration. The oxygen concentration is adjusted by controlling the atmosphere in each manufacturing step.

[0052] In general, rare earth-rich phases are formed by the precipitation of rare earth elements, T elements, and M elements at grain boundaries. The rare earth-rich phases magnetically separate the main phase particles, improving the HcJ of RTB permanent magnets.

[0053] If the oxygen concentration in each manufacturing process is high, the rare earth elements in the alloy powder obtained by pulverizing the raw alloy will be oxidized, resulting in the generation of oxides of the rare earth elements. The oxides of the rare earth elements are not reduced during sintering, and will precipitate in the form of oxides of the rare earth elements as they are at the grain boundaries. That is, the proportion of the rare earth elements that are not oxidized in each manufacturing process will decrease, and the volume proportion of the rare earth-rich phase will decrease. The volume proportion of the rare earth-rich phase that magnetically separates the main phase particles will decrease, and the HcJ of the resulting RTB permanent magnet will decrease. For this reason, for example, it is preferable to carry out each process (fine pulverization process, molding process) in an atmosphere with an oxygen concentration of 100 ppm or less.

[0054] (Fine grinding process) After the raw alloy is coarsely pulverized, the obtained coarsely pulverized powder of the raw alloy is finely pulverized until the average particle size is about several μm (fine pulverization process). As a result, fine pulverized powder of the raw alloy is obtained. The coarsely pulverized powder can be further finely pulverized to obtain fine pulverized powder. There is no particular restriction on the D50 of the particles contained in the fine pulverized powder. For example, D50 may be 2.0 μm or more and 4.5 μm or less, or 2.5 μm or more and 3.5 μm or less. The smaller the D50, the more likely it is that the HcJ of the RTB permanent magnet according to this embodiment will be improved. However, abnormal grain growth will be more likely to occur in the sintering process, and Hk / HcJ will be more likely to decrease. The larger the D50, the less likely it is that abnormal grain growth will be caused in the sintering process, and Hk / HcJ will be less likely to decrease. However, the more likely it is that the HcJ of the RTB permanent magnet according to this embodiment will be reduced.

[0055] Fine pulverization is performed by further pulverizing the coarsely pulverized powder using a fine pulverizer such as a jet mill, ball mill, vibration mill, or wet attritor while appropriately adjusting conditions such as pulverization time. The jet mill will be described below. A jet mill is a fine pulverizer that releases high-pressure inert gas (e.g., He gas, N2 gas, or Ar gas) from a narrow nozzle to generate a high-speed gas flow, and accelerates the coarsely pulverized powder of the raw alloy with this high-speed gas flow, causing collisions between the coarsely pulverized powder of the raw alloy and with a target or a container wall, thereby pulverizing the powder. A classifier may be attached to the jet mill. The particle size of the fine powder may be controlled by adjusting the operating conditions of the classifier.

[0056] A grinding aid may be added when the coarsely pulverized powder of the raw alloy is pulverized. There is no particular limit to the type of grinding aid. For example, an organic lubricant or a solid lubricant may be used. Examples of organic lubricants include oleic acid amide, lauric acid amide, and zinc stearate. Examples of solid lubricants include graphite. By adding a grinding aid, it is possible to obtain a finely pulverized powder that is likely to be oriented when a magnetic field is applied in the molding process. Either the organic lubricant or the solid lubricant may be used alone, or both may be used in combination. This is because the degree of orientation may decrease, especially when only a solid lubricant is used.

[0057] [Molding process] The finely pulverized powder is molded into a desired shape (molding process). In the molding process, the finely pulverized powder is filled into a die placed in an electromagnet and pressurized to mold the finely pulverized powder into a molded body. At this time, the finely pulverized powder can be molded in a state in which it is oriented in the direction of the easy axis of magnetization by molding while applying a magnetic field. As a result, a molded body in which the finely pulverized powder is oriented in the direction of the easy axis of magnetization is obtained. By using the molded body, an RTB-based permanent magnet with higher magnetic anisotropy can be obtained. In addition, a molding aid may be added. There is no particular limit to the type of molding aid. The same lubricant as the grinding aid may be used. In addition, the grinding aid may also serve as the molding aid. The molding process may be performed using a mold release agent or the like.

[0058] The pressure during pressurization may be, for example, 30 MPa or more and 300 MPa or less. The magnetic field to be applied may be, for example, 1000 kA / m or more and 1600 kA / m or less. The magnetic field to be applied is not limited to a static magnetic field, and may be a pulsed magnetic field. In addition, a static magnetic field and a pulsed magnetic field may be used in combination.

[0059] As a molding method, in addition to the dry molding in which the finely pulverized powder is molded as is as described above, wet molding in which a slurry in which the finely pulverized powder is dispersed in a solvent such as oil can also be applied.

[0060] The shape of the green body obtained by compacting the finely pulverized powder is not particularly limited, and can be, for example, a rectangular parallelepiped, a flat plate, a column, a ring, or any other shape that corresponds to the desired shape of the RTB permanent magnet.

[0061] [Sintering process] The green body obtained by molding into a desired shape is sintered in a vacuum or inert gas atmosphere to obtain an RTB permanent magnet (sintering step). The holding temperature and holding time during sintering need to be adjusted depending on various conditions, such as the composition (mainly the content of rare earth elements and B), the pulverization method, the particle size and particle size distribution, etc. The holding temperature may be, for example, 1000°C or more and 1100°C or less, or 1020°C or more and 1070°C or less. There is no particular limit to the holding time, but it may be, for example, 2 hours or more and 50 hours or less, or 4 hours or more and 40 hours or less. The shorter the holding time, the higher the production efficiency. There is no particular limit to the atmosphere during holding. For example, it may be an inert gas atmosphere, a vacuum atmosphere of less than 100 Pa, or a vacuum atmosphere of less than 10 Pa. There is no particular limit to the heating rate up to the holding temperature. By heating the green body, the finely pulverized powder contained in the green body is liquid phase sintered to obtain the RTB permanent magnet according to this embodiment. There is no particular restriction on the cooling rate after sintering the molded body to obtain a sintered body, but the sintered body may be rapidly cooled to improve production efficiency. The sintered body may be rapidly cooled at a rate of 30° C. / min or more.

[0062] [Aging treatment process] After sintering the compact, the RTB permanent magnet is subjected to an ageing treatment (aging treatment step). After sintering, the RTB permanent magnet obtained is subjected to an ageing treatment by, for example, holding the RTB permanent magnet at a temperature lower than the holding temperature in the sintering step. Below, a case where the ageing treatment is divided into two stages, a first aging treatment and a second aging treatment, is explained, but only one of the aging treatments may be performed, or three or more stages of aging treatment may be performed.

[0063] There is no particular limit to the holding temperature and holding time in each aging treatment. For example, the first aging treatment may be performed at a holding temperature of 800°C or more and 900°C or less for 30 minutes to 4 hours. The heating rate to the holding temperature may be 5°C / min to 50°C / min. The atmosphere during the first aging treatment may be an inert gas atmosphere (e.g., He gas, Ar gas) at atmospheric pressure or higher. The second aging treatment may be performed under the same conditions as the first aging treatment, except that the holding temperature may be 450°C or more and 550°C or less. The magnetic properties of the RTB permanent magnet can be improved by the aging treatment. The aging treatment process may be performed after the processing process described later.

[0064] [Cooling process] After the RTB permanent magnet is subjected to the aging treatment (first aging treatment or second aging treatment), the RTB permanent magnet is cooled in an inert gas atmosphere (cooling step). This makes it possible to obtain the RTB permanent magnet according to this embodiment. The cooling rate is not particularly limited. It may be 30°C / min or more.

[0065] [Processing process] The obtained RTB permanent magnet may be processed into a desired shape as necessary (processing step). Examples of processing methods include shaping such as cutting and grinding, and chamfering such as barrel polishing.

[0066] [Grain boundary diffusion process] A heavy rare earth element may be further diffused into the processed RTB permanent magnet (grain boundary diffusion step). There are no particular limitations on the method of grain boundary diffusion. For example, it may be carried out by applying a paint containing a heavy rare earth element compound to the surface of the RTB permanent magnet and then carrying out a heat treatment, or it may be carried out by attaching a compound containing a heavy rare earth element to the surface of the RTB permanent magnet by vapor deposition or the like and then carrying out a heat treatment. Grain boundary diffusion can further improve the HcJ of the RTB permanent magnet.

[0067] [Surface treatment process] The RTB permanent magnet obtained by the above steps may be subjected to surface treatment such as plating, resin coating, oxidation treatment, chemical conversion treatment, etc. (surface treatment step), which can further improve the corrosion resistance.

[0068] The RTB permanent magnet obtained in the above manner has a well-balanced improvement in Br and HcJ, and is an RTB permanent magnet with a high Hk / HcJ.

[0069] The present invention is not limited to the above-described embodiment, and various modifications can be made within the scope of the present invention. For example, in the method for producing an RTB permanent magnet, hot compaction and hot working may be performed instead of sintering.

[0070] There are no particular limitations on the applications of the RTB permanent magnets of the present invention. They are particularly suitable for use in motors and generators used near room temperature, such as voice coil motors and wind power generators. When used in such applications, the high Hk / HcJ makes it easy to increase the magnetic flux density of the magnet at the operating point of the motor. EXAMPLES

[0071] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0072] (Experimental Example 1) (Alloy preparation process) In the alloy preparation step, raw material alloys were prepared that would ultimately yield RTB permanent magnets having the compositions shown in Tables 1 to 5. The contents of all elements not listed in Tables 1 to 5, other than Fe, were less than 0.01 mass%.

[0073] First, raw metals containing predetermined elements were prepared. For example, the raw metals were appropriately selected and prepared from simple elements listed in Tables 1 to 5, alloys containing the elements listed in Tables 1 to 5, and / or compounds containing the elements listed in Tables 1 to 5.

[0074] Next, these raw metals were weighed and strip cast to prepare raw alloys from which magnets having the compositions shown in Tables 1 to 5 were ultimately obtained.

[0075] (Crushing process) In the pulverization process, the raw alloy obtained in the preparation process was pulverized to obtain alloy powder. The pulverization was carried out in two stages: coarse pulverization and fine pulverization. The coarse pulverization was carried out by hydrogen absorption pulverization. After the raw alloy was allowed to absorb hydrogen, it was dehydrogenated at 300 to 600°C in an argon flow or in a vacuum. The coarse pulverization produced alloy powder with a particle size of several hundred μm to several mm.

[0076] Fine pulverization was carried out using a jet mill after adding oleic acid amide as a grinding aid to 100 parts by mass of the alloy powder obtained by coarse pulverization and mixing. The amount of oleic acid amide added was controlled so that magnets having the compositions shown in Tables 1 to 5 were ultimately obtained. Nitrogen gas was used in the jet mill. Fine pulverization was carried out until the D50 of the alloy powder reached about 3.6 μm.

[0077] In sample No. 24, the amount of oxygen was significantly changed from the other experimental examples, and 500 ppm of oxygen gas was mixed with the nitrogen gas. In sample No. 25, the amount of oxygen was significantly changed from the other experimental examples, and 2000 ppm of oxygen gas was mixed with the nitrogen gas.

[0078] (molding process) In the compacting process, the alloy powder obtained in the pulverization process was compacted in a magnetic field to obtain a compact. The alloy powder was filled into a die placed in an electromagnet, and then pressed and compacted while applying a magnetic field from the electromagnet. The strength of the applied magnetic field was 1200 kA / m. The pressure during compacting was 40 MPa.

[0079] (Sintering process) In the sintering process, the obtained compact was sintered to obtain a sintered body. The holding temperature during sintering was 1070°C and the holding time was 4 hours. The sintering atmosphere was a vacuum atmosphere or an inert gas atmosphere.

[0080] (Aging process) In the aging step, the obtained sintered body was subjected to aging treatment to obtain an RTB permanent magnet. The aging treatment was carried out in two stages, a first aging treatment and a second aging treatment.

[0081] In the first aging treatment, the holding temperature was 850° C., the holding time was 1.0 hour, and the atmosphere during the first aging treatment was an Ar atmosphere.

[0082] The second aging treatment was performed at a holding temperature of 480° C. for 1.5 hours in an Ar atmosphere.

[0083] It was confirmed by composition analysis using X-ray fluorescence analysis, inductively coupled plasma mass spectrometry (ICP method), and gas component analysis that the compositions of the RTB permanent magnets finally obtained in each of the Examples and Comparative Examples were those shown in Tables 1 to 5. In particular, the C content was measured by oxygen flow combustion-infrared absorption method. The B content was also measured by ICP method.

[0084] (evaluation) The magnetic properties of the RTB permanent magnets made from the raw alloys of each of the Examples and Comparative Examples were measured using a BH tracer. The magnetic properties measured were Br, HcJ, and Hk / HcJ. The results are shown in Tables 1 to 5.

[0085] In the RTB permanent magnet of this embodiment, a magnet was deemed "good" if it satisfied all of the following criteria: Br of 1450mT or more, HcJ of 1200kA / m or more, and Hk / HcJ of 95% or more. With regard to Br, a magnet was deemed "even better" if it was 1460mT or more. With regard to HcJ, a magnet was deemed "even better" if it was 1320kA / m or more, and "particularly good" if it was 1350kA / m.

[0086] [Table 1]

[0087] [Table 2]

[0088] [Table 3]

[0089] [Table 4]

[0090] [Table 5]

[0091] Table 1 shows examples and comparative examples in which TRE or Pr / TRE was mainly changed. The examples in which TRE was 29.00 mass% or more and 31.00 mass% or less and Pr / TRE was 0.30 or more and 0.50 or less had good magnetic properties. The examples in which TRE was 30.00 mass% or more and 31.00 mass% or less and Pr / TRE was 0.40 or more and 0.50 or less had good magnetic properties, especially HcJ. In contrast, the comparative examples in which TRE was too small and the comparative examples in which Pr / TRE was too small had low HcJ. The comparative examples in which TRE was too large had low Br. The comparative examples in which Pr / TRE was too large had low Hk / HcJ.

[0092] Table 2 shows examples and comparative examples in which the B content, C content or O content was mainly changed. Each example in which the contents of all elements were within the specified range had good magnetic properties. Each example in which the B content was 0.95 mass% or less, the C content was 0.09 mass% or less, and the O content was 0.04 mass% to 0.10 mass% had good magnetic properties, especially HcJ. In contrast, the comparative example in which the B content was too small had a reduced Hk / HcJ. The comparative example in which the B content was too large had a reduced HcJ. The comparative example in which the C content was too large had a reduced HcJ. The comparative example in which the O content was too large had a reduced HcJ.

[0093] Table 3 shows examples and comparative examples in which the M content and Cu content were mainly changed. The magnetic properties were good in each example in which the contents of all elements were within the specified range. In contrast, the comparative example in which the M content was too small had a reduced HcJ. The comparative example in which the M content was too large had a reduced Br.

[0094] Furthermore, the examples in which the M content was 0.50 mass% or more and 1.00 mass% or less had improved HcJ compared to the examples in which the M content was less than 0.50 mass%. The examples in which the M content was 0.50 mass% or more and 1.00 mass% or less had improved Br compared to the examples in which the M content was more than 1.00 mass%.

[0095] Examples in which the M content was 0.50 mass% or more and 1.00 mass% or less and the Cu content was 0 mass% or more and 0.19 mass% or less showed particularly improved HcJ, compared with examples in which the M content was 0.50 mass% or more and 1.00 mass% or less and the Cu content exceeded 0.19 mass%.

[0096] Furthermore, in each of the examples in which the M content was 0.65 mass % or more and 1.00 mass % or less and the Cu content was 0.05 mass % or more and 0.20 mass % or less, HcJ was particularly improved compared to the other examples.

[0097] Examples in which the M content exceeded 1.00 mass% and the Cu content was 0 mass% or more and 0.20 mass% or less showed particularly improved HcJ, compared with examples in which the M content exceeded 1.00 mass% and the Cu content exceeded 0.20 mass%.

[0098] Table 4 shows examples in which the Co content, Pr / C, or B+C were mainly changed. Each example in which the contents of all elements were within the specified range had good magnetic properties. In particular, the magnetic properties were further improved when the Co content was 1.10 mass% or more and 1.50 mass% or less, Pr / C was 100 or more and 400 or less, and B+C was 0.93 or more and 1.07 or less.

[0099] Table 5 shows examples and comparative examples in which the type and content of RH was mainly changed. The examples in which the content of all elements was within the specified range had good magnetic properties. In contrast, the comparative examples in which the content of RH was too high had a reduced Br.

Claims

1. An R-T-B system permanent magnet containing a rare earth element, a transition metal element, boron, and M, The rare earth elements include at least Nd and Pr, The transition metal element contains at least Fe and Co, M is one or more selected from Al, Cu, Ga, and Zr; The content of the rare earth element on a mass basis is defined as TRE, and the value obtained by dividing the content of Pr on a mass basis by TRE is defined as Pr / TRE. TRE is 29.00% by mass or more and 31.00% by mass or less, a content of heavy rare earth elements of 0% by mass or more and 0.20% by mass or less; Pr / TRE is 0.30 or more and 0.50 or less, The Co content is 1.10 mass% or more and 1.50 mass% or less, a boron content of 0.90% by mass or more and 1.00% by mass or less; a carbon content of 0% by mass or more and 0.10% by mass or less; The oxygen content is 0% by mass or more and 0.15% by mass or less, The nitrogen content is 0% by mass or more and 0.15% by mass or less, An RTB-based permanent magnet having an M content of 0.30 mass % or more and 1.50 mass % or less.

2. 2. The RTB system permanent magnet according to claim 1, wherein Pr / C is 100 or more, where Pr / C is the Pr content by mass divided by the carbon content by mass.

3. An R-T-B system permanent magnet as described in claim 1, in which Pr / C is 120 or more, where Pr / C is the Pr content by mass divided by the carbon content by mass.

4. An R-T-B system permanent magnet as described in claim 1, wherein Pr / C is the Pr content by mass divided by the carbon content by mass, and Pr / C is 120 or more and 600 or less.

5. An R-T-B system permanent magnet containing a rare earth element, a transition metal element, boron, and M, The rare earth elements include at least Nd and Pr, The transition metal element contains at least Fe, or Fe and Co, M is one or more selected from Al, Cu, Ga, and Zr; The content of the rare earth element on a mass basis is defined as TRE, the value obtained by dividing the content of Pr on a mass basis by TRE is defined as Pr / TRE, and the value obtained by dividing the content of Pr on a mass basis by the content of carbon on a mass basis is defined as Pr / C. TRE is 29.00% by mass or more and 31.00% by mass or less, a content of heavy rare earth elements of 0% by mass or more and 0.20% by mass or less; Pr / TRE is 0.30 or more and 0.50 or less, Pr / C is 120 or more and 600 or less, a boron content of 0.90% by mass or more and 1.00% by mass or less; the carbon content is 0.02% by mass or more and 0.10% by mass or less; The oxygen content is 0% by mass or more and 0.15% by mass or less, The nitrogen content is 0% by mass or more and 0.15% by mass or less, An RTB-based permanent magnet having an M content of 0.30 mass % or more and 1.50 mass % or less.

6. 6. The RTB system permanent magnet according to claim 1, wherein the Cu content is 0% by mass or more and 0.20% by mass or less.

7. 6. The RTB system permanent magnet according to claim 1, wherein the total content of boron and carbon is 0.93 mass % or more and 1.07 mass % or less.

8. 6. The RTB system permanent magnet according to claim 1, wherein the M content is 0.50 mass % or more and 1.00 mass % or less.